An Analysis of Public Knowledge, Attitudes, and Practices Regarding Cigarette Smoking: A Cross-Sectional Survey of Residents in Lahore, Pakistan - Zaheer, Ifra; Shahzad, Huma; Fatima, Faseeha; Ali, Farhad; Veesar, Attaullah (Symbiohealth, 2026)
Tobacco smoking remains a formidable public health challenge in low- and middle-income countries like Pakistan. This cross-sectional study aimed to assess the knowledge, attitudes, and practices (KAP) regarding cigarette smoking among 800 residents of Lahore, selected via a multi-stage sampling technique. The findings reveal a smoking prevalence of 23%, with initiation primarily occurring in late adolescence (mean age 19.2 years) and driven predominantly by peer pressure (75%) and stress relief (56.3%). While knowledge of major health risks like lung cancer was high (94%), a significant gap existed between this knowledge and personal risk perception, alongside the powerful influence of socio-cultural norms, including the high social acceptability of male smoking (75.5%) and the perceived efficacy of smoking for stress relief (81.8%). The study concludes that despite adequate awareness, smoking behavior in Lahore is sustained by deep-rooted social and cultural factors, underscoring the urgent need for public health interventions that extend beyond informational campaigns to address these normative and psychological drivers.